Long-distance propagation of short-wavelength spin waves - Chuanpu Liu; Jilei Chen; Tao Liu; Florian Heimbach; Haiming Yu; Yang Xiao; Junfeng Hu; Mengchao Liu; Houchen Chang; Tobias Stueckler; Sa Tu; Youguang Zhang; et al. (Nature Communications, 2018)
Short-wavelength spin waves with high group velocity are one of the key ingredients for the spin-wave based memory-logics. Here the authors demonstrate the propagation of spin waves with wavelength down to 50 nm and group velocity up to 2600 m s−1 using ferromagnetic nanowires grown on a thin Y3Fe5O12 film strip structure.